PENGARUH KEPUASAN KERJA, KUALITAS KEHIDUPAN KERJA DAN PRESTASI KERJA TERHADAP KINERJA GURU DI MTS AL JAMIYATUL WASLIYAH TEMBUNG - Muhammad Ihsan; Syukril Jamil Harahap; Husniati .; Dayatullah .; Masrida . (Jurnal Prodi Fakultas Ekonomi-UISU, 2021)
The formulation in this study is how the influence ofjob satisfaction,quality of work life and work achievement on teacher performance. The purpose of this study was to find out and analyze the effect ofjob satisfaction, quality of work life and work achievement on teacher performance. This research is a descriptive quantitative research. Data collection techniques are carried out through interviews, lists of questions and documentation studies. The sample in this study was 67 teachers. Variables are measured on a Likert scale. Hypothesis testing using multiple linear regression analysis through F test and t test.Simultaneous test results showed that job satisfaction, work quality and work achievement had a significant effect on teacher performance variables. In part, job satisfaction has a positive and significant effecton teacher performance, quality of work life has a positive and significant effecton teacher performance and work achievement has a positive and significant effect on teacher performance.